Projeto Político-Pedagógico: construção e implicações a partir dos enunciados dos docentes de Ensino Religioso das escolas municipais de João Pessoa-PB - Guedes, Márcia Lustosa Felix (2012)
This study aimed at analyzing the contributions of the Religious Teaching teachers for the Political-pedagogical Project of some schools of the Municipal Teaching System. For the fulfillment of the research, interviews carried out with six teachers of six different municipal schools and personal notes about the pedagogical practice of these professionals were considered. For the theoretical approach, Bardin´s (2010) ideas, referring to Content Analysis, were used as well as Veiga´s (1995; 2001), Escarião´s (2001) and Vasconcellos´ ones (2002), among other authors, concerning the principles of the Political-pedagogical Project. Results revealed that the Political-pedagogical Project contributes meaningfully to the enhancement of the Religious Teaching subject, though it still requires experience of the school community for constructing a permanent practice of reflection about the educational actions involving the students´ critical formation.